2018
DOI: 10.1164/rccm.201804-0682ci
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis and Overdiagnosis of Asthma

Abstract: Asthma is diagnosed on the basis of respiratory symptoms of wheeze, cough, chest tightness, and/or dyspnea together with physiologic evidence of variable expiratory airflow limitation. The prevalence of asthma varies widely around the world, ranging from 0.2% to 21.0% in adults and from 2.8% to 37.6% in 6- to 7-year-old children. Population-based studies in children, adults, and the elderly suggest that from 20% to 70% of people with asthma in the community remain undiagnosed and hence untreated. Underdiagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
185
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(197 citation statements)
references
References 52 publications
3
185
2
7
Order By: Relevance
“…in accordance with what Aaron et al 7 reviewed for schoolchildren worldwide. Also, the present study provided evidence of under-diagnosed asthma in both settings (urban and rural), confirming that asthma diagnosis merely based on reported symptoms may be underestimating the real prevalence of this disease, as previously reported in the literature.…”
supporting
confidence: 87%
“…in accordance with what Aaron et al 7 reviewed for schoolchildren worldwide. Also, the present study provided evidence of under-diagnosed asthma in both settings (urban and rural), confirming that asthma diagnosis merely based on reported symptoms may be underestimating the real prevalence of this disease, as previously reported in the literature.…”
supporting
confidence: 87%
“…10 We could not find any US-based study, but a recent systematic review on this topic reported that studies across different jurisdictions have consistently reported an overdiagnosis rate between 29% and 34%. 45 Our threshold analysis also indicated that the overdiagnosis rate in the US should be implausibly low for the diagnostic verification to not be cost-saving. We assumed that diagnostic verification would take place in the context of routine clinical practice, and as such, our results do not pertain to alternative schemes such as a systematic screening program.…”
Section: Discussionmentioning
confidence: 77%
“…Different approaches to improve case finding in OLD have been investigated [7][8][9][10] . Especially among younger individuals, it can be difficult to predict the future risk of developing OLD, as disease progression is usually slow and can be influenced by more risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…npj Primary Care Respiratory Medicine (2020)10 Published in partnership with Primary Care Respiratory Society UK 1234567890():,;…”
mentioning
confidence: 99%